FGF signaling in cranial suture development and related diseases - Zhao, Xiaolei; Erhardt, Shannon; Sung, Kihan; Wang, Jun (Frontiers in Cell and Developmental Biology, 2023)
Suture mesenchymal stem cells (SMSCs) are a heterogeneous stem cell population with the ability to self-renew and differentiate into multiple cell lineages. Cranial suture provides a niche for SMSCs to maintain suture patency, allowing for cranial bone repair and regeneration. In addition, cranial suture functions as an intramembranous bone growth site during craniofacial bone development. Defects in suture development have been implicated in various congenital diseases, such as sutural agenesis and craniosynostosis. However, it remains largely unknown how intricate signaling pathways orchestrate suture and SMSC function in craniofacial bone development, homeostasis, repair, and diseases. Studies in patients with syndromic craniosynostosis identified fibroblast growth factor (FGF) signaling as an important signaling pathway that regulates cranial vault development. A series of in vitro and in vivo studies have since revealed the critical roles of FGF signaling in SMSCs, cranial suture and cranial skeleton development, and the pathogenesis of related diseases. Here, we summarize the characteristics of cranial sutures and SMSCs, and the important functions of the FGF signaling pathway in SMSC and cranial suture development as well as diseases caused by suture dysfunction. We also discuss emerging current and future studies of signaling regulation in SMSCs.